Biaya Perawatan Kendaraan Mobil Pada Mikha Rental CV Almi’ra Regency - Iis Rahayu; Inna Pujiana Yuniar; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
With increasing development in all fields, especially in the economic field, transportation facilities are currently one of the economic linkages that are also experiencing rapid progress. engaged in the field of car rental services, CV Almira regency rents out various types of vehicles such as Avanza, Mazda 2, Agya, Senia, Rush, Mobillio. Companies engaged in the transportation sector must pay attention to vehicle maintenance costs. Cost is the loss of economic resources, measured in monetary units, that is incurred or may be incurred to achieve a specified objective. Fees are exchange rates, conditions, or sacrifices that are paid to obtain benefits. This cost is understood as the sum of all the labor and costs involved in developing, manufacturing, and using the product used for routine maintenance and service. At the mica rental company CV Al'mira regency, there are 35 types of spare parts that must be replaced in the last 1 month and the total amount for that 1 month is IDR 12,870,000. Securing security and others.